Scrub typhus in northern Thailand - Wangrangsimakul, T (2021)
Scrub typhus, a neglected infectious disease caused by obligate intracellular bacteria Orientia tsutsugamushi, is a major cause of acute non-malarial fever in the tropics. Difficulties surrounding diagnosis have hampered our understanding of disease burden, which in turn negatively impacts awareness. Using national surveillance data, I highlighted the high burden of scrub typhus in Thailand with a substantial rise in cases over time. Spatially, disease burden was greatest in the northern region and geographical and meteorological factors may contribute to disease prevalence. Scrub typhus contributes significantly to the febrile disease burden in Chiangrai, northern Thailand, with 22.5% of adults admitted to hospital with acute undifferentiated fever diagnosed with the disease. I described the disease in adults and found presence of eschar and elevated liver enzymes to be predictive of scrub typhus. Scrub typhus in children remains understudied and in this thesis, I characterised paediatric scrub typhus in Chiangrai, showing that the disease was frequently severe and potentially fatal with complication and treatment failure rates of 40% and 23%, respectively. Severe hepatitis was found to be predictive of treatment failure in this cohort.